Pseudoangiomatous variant of spindle cell lipoma: Report of a rare case - Amoolya Bhat; C Vijaya; Suraksha B Rao (Wolters Kluwer Medknow Publications, 2016)
Pseudoangiomatous spindle cell lipoma is a rare variant of spindle cell lipoma. It exhibits irregular and branching spaces with villiform connective tissue projections, leading to formation of a characteristic angiomatoid pattern in addition to benign spindle cells and mature adipocytes. Recent studies have shown that these branching spaces are lined by endothelial cells and express markers. Therefore, the term "angiomatous variant" instead of "pseudoangiomatous" has been proposed for these lesions. We describe one of such lesions in the thumb of a young female. To the best of our knowledge, this is the first reported case of pseudoangiomatous variant of spindle cell lipoma from India.